Academic Writing with GenAI: Professional Development Needs in Higher Education - McGury, Sandra; Wulff , Nadja; Häusler, Anja (Journal of Academic Writing, 2025)
Academic writing has always posed a challenge to university students, regardless of the language they are writing in (first, second or foreign language) or the amount of digital support they have access to – for example, online dictionaries, thesauruses, or new generative artificial intelligence (GenAI) software such as ChatGPT. With the rise of GenAI as a legitimate digital tool in higher education, it is crucial to identify the professional development needs of teaching faculty in order to ensure quality teaching. Based on factors such as digital literacy, or access to digital tools, these needs might differ in various geographical regions. Within the context of the European Framework for the Digital Competence of Educators (DigCompEdu), this paper aims to provide a differentiated, international student perspective on the use of GenAI in the academic writing process, identifying professional development needs for faculty. We developed an online questionnaire that was filled out by 192 university students from 15 different countries. In addition to their academic and linguistic backgrounds, the respondents answered questions about their own experiences and competences with the use of GenAI within academic research. Results highlight clear discrepancies between geographic regions, for example, in their self-ranked digital proficiency or in what GenAI tools they use. This, along with further results from the analysis, provides the basis to identify some professional development needs.